Enhanced in vitro antibacterial effect against Enterococcus faecalis by using both low-dose cetylpyridinium chloride and silver ions - Silei Lv; Wei Fan; Bing Fan (BMC Oral Health, 2023)
Abstract Background Enterococcus faecalis (E. faecalis) is frequently isolated from root canals with failed root canal treatments. Due to the strong ability of E. faecalis to resist many often-used antimicrobials, coping with E. faecalis infections remains a challenge. The aim of this study was to investigate the synergistic antibacterial effect of low-dose cetylpyridinium chloride (CPC) and silver ions (Ag+) against E. faecalis in vitro. Methods The minimum inhibitory concentration (MIC), minimum bactericidal concentration (MBC) and the fractional inhibitory concentration index (FICI) were used to confirm the existence of the synergic antibacterial activity between low-dose CPC and Ag+. Colony-forming unit (CFU) counting, time-killing curve and dynamic growth curve were used to evaluate the antimicrobial effects of CPC and Ag+ combinations against planktonic E. faecalis. Four weeks biofilms were treated with drug-contained gels to determine the antimicrobial effect on biofilm-resident E.faecalis, and the integrity of E.faecalis and its biofilms were observed by FE-SEM. CCK-8 assays was used to test the cytotoxicity of CPC and Ag+ combinations on MC3T3-E1 cells. Results The results confirmed the synergistic antibacterial effect of low-dose CPC and Ag+ against both planktonic and 4-week biofilm E. faecalis. After the addition of CPC, the sensitivity of both planktonic and biofilm-resident E. faecalis to Ag+ improved, and the combination showed good biocompatibility on MC3T3-E1 cells. Conclusions Low-dose CPC enhanced the antibacterial ability of Ag+ against both planktonic and biofilm E.faecalis with good biocompatibility. It may be developed into a novel and potent antibacterial agent against E.faecalis, with low toxicity for root canal disinfection or other related medical applications.